Method Development and Validation of Cefixime by Using RP-HPLC in Pharmaceutical Formulations (International Journal of Research in AYUSH and Pharmaceutical Sciences, 2023)
Analytical method development and validation are ongoing and interconnected activities that are essential in research and development, quality control, and quality assurance departments. They involve the creation and testing of analytical procedures to assess equivalence and manage risks effectively. These procedures are crucial for establishing specific acceptance criteria for products and ensuring the reliability and consistency of results. Validations are essential in assessing whether an analytical procedure is appropriate and reliable for its intended purpose. Literature survey reveals that the analytical methods based on UV spectrometry, RP-HPLC and HPTLC for the determination of Cefixime individually and combination with others drugs . The methods were validated according to ICH guidelines in terms of accuracy, precision, lod, and other aspects of analytical validation. The developed analytical methods for cefixime have been designed to be straightforward, making them easy to perform. They have also demonstrated high sensitivity, enabling the detection and quantification of cefixime at low concentrations. This sensitivity is crucial for accurately determining the amount of cefixime present in bulk samples or tablet formulations.
Keywords: Cefixime, RP-HPLC, Accuracy, Precision, Validation.